High Resolution, High Capacity, Spatial Specificity in Perceptual Learning - Le Dantec, Christophe; Seitz, Aaron (Frontiers in Psychology, 2012)
Research of perceptual learning has received significant interest due to findings that training on perceptual tasks can yield learning effects that are specific to the stimulus features of that task. However, recent studies have demonstrated that while training a single stimulus at a single location can yield a high-degree of stimulus specificity, training multiple features or at multiple locations can reveal a broad transfer of learning to untrained features or stimulus locations. We devised a high-resolution, high-capacity, perceptual learning procedure with the goal of testing whether spatial specificity can be found in cases where subjects are highly trained to discriminate stimuli in many different locations in the visual field. We found a surprising degree of location specific learning, where performance was significantly better when target stimuli were presented at one of the twenty-four trained locations compared to when they were placed in one of the twelve untrained locations. This result is particularly impressive given that untrained locations were within a couple degrees of visual angle of those that were trained. Given the large number of trained locations, the fact that the trained and untrained locations were interspersed, and the high-degree of spatial precision of the learning, we suggest that these results are difficult to account for using attention or decision strategies and instead suggest that learning may have taken place for each location separately in retinotopically organized visual cortex.